Keyboard Interpretation from the 14th to the 19th Century: An Introduction - Ferguson, Howard 1908-1999 (London Oxford University Press, 1979)
This standard work is an introduction to the interpretation of keyboard music from the fourteenth to the nineteenth century. Dr Ferguson provides information about the instruments themselves, and discusses this vast, fascinating, and ever-changing subject under the headings: musical types and forms, tempo, phrasing and articulation, fingering, rhythmic conventions, the `tones' or modes, ornamentation, pianists' problems, and editors' problems. It is a clear, detailed, and practical guide to authenticity in performance which all keyboard players will find indispensable. This reissue incorporates an updated list of modern editions and a completely revised bibliography.
Keywords: Middle Ages (500-1400); Renaissance (1400-1600); 17th Century (1601-1700); 18th Century (1701-1800); 19th Century (1801-1900); Keyboard instrument; Keyboard music; Musical interpretation